Application of the methods of physical rehabilitation in the treatment of women with hyperprolactinemia - Gagara V.F; Mirnaya A.І; Sakhnenko H.P (Kharkov National Pedagogical University, 2013)
Purpose: The results of studies of the effectiveness effects on the body of women with reproductive dysfunction and hyperprolactinemia matched set of methods of physical rehabilitation. Material/Methods: The study involved 24 women aged 18-38 years who were equally divided into study and control groups. Women in both groups received complex rehabilitation measures, which included intravenous laser irradiation of blood on the combined laser therapy apparatus "MIT-1." The procedure was performed every day, the course of 10 sessions, duration - 20 min. The patients of the main group along with radiation listened relaxing sounds (classical music, the noise of the sea, rain) and performed their own range of therapeutic exercise, aimed at speeding up the metabolism. Results: The study found that patients in both groups of women (91.7%) under the influence of rehabilitation measures significantly reduced the level of prolactin in the blood, which almost returned to normal. Intravenous laser irradiation of blood goes well with listening to relaxing music and the use of therapeutic exercise. Conclusion: The use of intravenous laser irradiation of blood in conjunction with listening to relaxing music and the use of a complex exercise significantly reduces the level of prolactin in women with hyperprolactinemia.